Pengaruh Struktur Modal dan Ukuran Perusahaan Terhadap Agency Cost dan Kinerja Perusahaan (Studi Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia) - Dewi Maryam (ITB AAS INDONESIA, 2018)
This study aims to examine the effect of capital structure, the size of the company to the agency cost and performance of the company. In addition, the indirect influence between capital structure and size of the company to the agency cost is also researched in this study. The study population used in this study were 18 companies in the consumer goods industry sectors listed on the Indonesia Stock Exchange (BEI) in the study period 2010-2014. Number of sample as the number of population by census method. This study analysis method is path analysis using SPSS software. The results of this study show that there is significant influence negatively the size of the company to the agency cost and there is significant influence negatively agency cost to company performance, there is no influence between capital structure to agency cost and there is no influence of capital structure to the company's performance, and there is no effect of firm size on company performance.